Opportunity and Challenges for the Application of the Independent Learning Curriculum to Islamic Education in Madrasah - Tantri, Risa; Gusrita, Silvia; Sakti, Faradiela; Hendrizal, Hendrizal (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2024)
Madrasah in Indonesia faces opportunities and challenges in keeping up with current developments to achieve quality education. The independent learning curriculum is the latest development in education in Indonesia. This curriculum carries the concept of flexibility, giving teachers freedom in choosing learning methods and materials. This research analyzes problems in applying the independent learning curriculum to Islamic education in Madrasah. This research method uses literature or library research with a descriptive analysis approach. Data collection techniques involve information sources from various relevant literature and documents. This research shows that the independent learning curriculum can provide students with a deep and comprehensive learning experience if implemented comprehensively in Madrasah. However, several problems arise when implementing the curriculum. Issues such as the readiness of teachers and staff, the quality and consistency of Islamic education, and adequate resources are the main problems among the many problems in implementing the independent curriculum for Islamic madrasah education. In overcoming this problem, there is a need for additional training for teachers and staff, the development of curriculum consistency guidelines, and an emphasis on the continuation of quality Islamic education.